PERSEPSI PETANI TERHADAP PEMBUKAAN LAHAN TANPA PEMBAKARAN (PLTB) DI KELURAHAN SAGATANI KECAMATAN SINGKAWANG SELATAN - Sri Widarti; Donna Youlla; Icuk Setiawan (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
People's perceptions of land clearing by burning are still diverse, there are pros and cons about it. As we all know, the land clearing system by slashing and burning is a heritage and culture of farming communities in almost all parts of Indonesia, one of them is the people of the island of Kalimantan. Several solutions have been proposed by the government, including land clearing without burning (PLTB). This program aims to change the behavior of Indonesian farmers who still do land clearing by burning to switch to more environmentally friendly land clearing methods, including converting slashes into compost and wood vinegar. However, until now several programs launched by the government in order to minimize the forest and land fires have not been successful. Increasing the production of hybrid corn commodities is one of the targets for increasing agricultural productivity in West Kalimantan, especially in Singkawang in meeting the demand for hybrid corn which is currently supplied from outside the city. The increase in production cannot be separated from the need for expansion of hybrid corn farming land, which currently the number and focus of increasing hybrid corn farming businesses are in Sagatani Village, South Singkawang District. Problems arise when in their business, hybrid corn farmers in Sagatani Village still use conventional methods in cleaning and clearing land, namely by burning.